ANALYSIS OF ABILITY OF TOILET TRAINING IN PRESCHOOLS CHILDREN AT EARLY CHILDHOOD EDUCATION DARUSSALAM PUNDUNGAN JUWIRING - Witriyani . (STIKES DUTAGAMA KLATEN, 2017)
Background: Growth and development in a child normally does not equal between children who are one with the other. Parents can provide stimulation to the child at the time of gold because it will be more optimal. Trained in hygiene themselves such as urination and defecation in place is very important to be taught. Toilet training can generally be implemented on every child who has already entered the phase of independence in children and can be implemented early to rehearse response to ability to defecate and small.The purpose of the research: Analyze the ability of Toilet Training in children in early childhood education Darussalam Pundungan Juwiring. Research methods: This research is descriptive research through the approach of cross sectional with respondent as much as 80 children. Research done by observations indirectly using questionnaires shaped check list which will be filled by the respondent. Research results: Toilet training abilities in children in early childhood education Pundungan Darussalam Juwiring that high as much as 58.75 (47%), with the capability of being as much as 33 children (41.25%) and no child is capable of is low. Conclusion: Analysis of abilities of toilet training in preschools children at early childhood education DarussalamPundungan Juwiring that is children who have the ability in toilet training as many as 80 children (100%) and in general all children have the ability in toilet training.